Mortality, Transmitter Retention, Growth, and Wound Healing in Juvenile Salmon Injected with Micro Acoustic Transmitters. Issue 5 (2nd September 2016) - Liss, Stephanie A.; Brown, Richard S.; Deters, Katherine A.; Walker, Ricardo W.; Deng, Z. Daniel; Eppard, M. Brad; Townsend, Richard L.; Seaburg, Adam G.
Abstract: A cylindrical micro acoustic transmitter (AT; weight in air = 0.2 g) has been developed for injection into the peritoneal cavity of fish. Laboratory studies can provide tagging guidelines to minimize the effects of implantation techniques and transmitter burden (transmitter weight expressed as a proportion of fish weight) before use of the AT in field studies. To establish guidelines for minimizing tagging effects, we examined response variables (mortality, transmitter expulsion, growth, and wound healing) for micro AT-injected juvenile Chinook Salmon Oncorhynchus tshawytscha over a wide range of sizes (65–104 mm FL). The overarching goal was to determine a minimum size threshold at which the adverse effects of micro AT injection on fish are minimized. Juveniles ( n = 700) were separated into four treatments: (1) AT injection, (2) injection of an AT and a PIT tag (AT+PIT), (3) injection of visible implant elastomer (marked control), and (4) unmarked (true) control. Fish were evaluated once per week for 4 weeks and at the end of the study (60 d posttagging). The AT- and AT+PIT-injected fish experienced greater mortality than marked controls and grew (FL and weight gain) significantly less than marked controls, although no minimum size thresholds were detected. By 60 d posttagging, the transmitter expulsion rate was 44% for AT-injected fish and 20% for AT+PIT-injected fish. However, among the 90-mm and larger fish in the AT treatment, none died or expelled a transmitter. Initial FL significantly affected wound healing for both injection treatments. A size threshold (85.1 mm FL) was identified for AT+PIT-injected fish at 7 d posttagging, indicating that wound areas in fish smaller than 85.1 mm were larger than the wound areas in fish exceeding 85.1 mm. Our results suggest that AT or AT+PIT injection had a greater effect on smaller juvenile Chinook Salmon than on larger fish. Received January 25, 2016; accepted April 7, 2016 Published online August 16, 2016